Pemberdayaan Ekonomi Umat Melalui Pengelolaan Dana Zakat Produktif - Sumarni, Sumarni; Jumasrah, Jumasrah; Rahayu, Irma; Qalbi, Nurul (Jurnal Maps (Manajemen Perbankan Syariah), 2024)
National Amil Zakat Agency (BAZNAS)  is one of the government institutions that formally has the right and obligation to manage zakat funds in order to create effectiveness in zakat fund management services and can also increase the benefits of zakat for humanity in order to improve economic prosperity. BAZNAS Kolaka Regency with the qardhul hasan financing program cannot be said to be successful because of the problem of many mustahik who are delinquent and do not return the qardhul hasan funds caused by the absence of collateral on qardhul hasan financing. This type of research is descriptive, that is, with this method it is hoped that it can identify why and how a phenomenon occurs. The results of this research show that economic empowerment of the people through productive zakat fund management has been realized quite well, and namely the ZMart program (Zakat Mart), the utilization of productive zakat funds can be said to be successful in increasing economic empowerment.